Two new species of Psen Latreille, 1796 (Hymenoptera, Apoidea, Crabronidae) from China, with a key to Psen species of China - Yao Deng; Li Ma; Qiang Li (ZooKeys)
Two new species of the genus Psen Latreille, 1796, namely Psen fronistriatus sp. nov. and Psen scabrosus sp. nov. are described and illustrated from China. A key to the Chinese species of Psen is also provided.